Influence of dietary sodium alginate and Pediococcus acidilactici on liver antioxidant status, intestinal lysozyme gene expression, histomorphology, microbiota, and digestive enzymes activity, in Asian sea bass (Lates calcarifer) juveniles - Ghasem Ashouri (2020)
© 2019 Elsevier B.V. A 42-day study was conducted to determine the effect of incorporating dietary low molecular weight sodium alginate (LMWSA), extracted from the brown algae, Undaria pinnatifida and Macrocystis pyritera, and Pediococcus acidilactici MA 18/5 M (PA), Lallemand Animal Nutrition S.A., Blagnac, France, on growth performance, antioxidant defense activity, intestinal lysozyme gene (LYZ) expression, histo-morphology, microbiota, and digestive enzymes activity of Asian sea bass (Lates calcarifer) juveniles. Six experimental diets were formulated including: Diet (1) a basal diet (Control), Diet (2) 5 g LMWSA kg−1 diet, Diet (3) 10 g LMWSA kg−1 diet, Diet (4) 0.9 × 107 CFU PA g−1 diet, Diet (5) 5 g LMWSA kg−1 diet + 0.9 × 107 CFU PA g−1 diet, and Diet (6) 10 g LMWSA kg−1 diet + 0.9 × 107 CFU PA g−1 diet were fed to Asian sea bass, L. calcarifer (12.0 ± 0.2 g). The results showed that fish fed PA alone (Diet 4) and the combination of both supplements (Diet 5) had the greatest weight gain. Fish fed Diet 6 and those fed Diet 1 (Control) had the highest and lowest villus height, apparent villus surface and crypt depth, respectively. Fish fed diets administered with PA (Diet 4) or synbiotics (Diets 5 and 6) showed higher total viable and lactic acid bacteria counts than all the other groups. The evaluated digestive enzymes activities including total protease, trypsin, lipase, and α-amylase remarkably increased by administration of LMWSA or its combination with PA. Moreover, liver antioxidant enzymes activities including superoxide dismutase, catalase, and Glutathione S-transferase pronouncedly enhanced following the administration of LMWSA or its combination with PA. Supplementing diet with blends of 10 g kg−1 of LMWSA and PA (Diet 6) more pronouncedly enhanced c-type and g-types LYZ expression in comparison with those fed 5 g kg−1 of LMWSA and PA (Diet 5). Based on the results obtained, it can be claimed incorporating diet with LMWSA and PA separately or in symbiotic form had promising results as functional feed additives in juvenile Asian sea bass L. calcarifer.